Fiqh Learning Strategies to Improve Student Achievement at Islamic Junior High School - Hidayat, Rohmat; Zamroni, Ahmad; Darmawan, Moh. Faridl (SCHOOLAR: Social and Literature Study in Education, 2024)
This study aims to explore the strategies used by teachers in the classroom, identify the obstacles they face, and the solutions they use to overcome these obstacles. This study used a descriptive qualitative approach with data collection methods through interviews, observation, and documentation. Data analysis was conducted through the stages of collecting, processing, analyzing, and drawing conclusions. Data validity was maintained through several techniques, namely: 1). careful observation; 2). extended research time; 3). triangulation. The conclusions of this research are: 1) Fiqh teachers use strategies that improve student achievement, such as strategies in opening and closing lessons, classroom management, delivery of materials, providing reinforcement, use of methods, and evaluation; 2). The obstacles they face include difficulties in classroom management due to a lack of interaction between teachers and students, teachers' readiness in the learning process, teachers' understanding of students' characteristics, students' lack of understanding of Fiqh, and limited learning resources; 3). The efforts made by teachers to overcome these obstacles include improving interaction with students.